Mid-infrared quantum cascade detectors for applications in spectroscopy and pyrometry - Hofstetter, Daniel; Giorgetta, Fabrizio R.; Baumann, Esther; Yang, Quankui; Manz, Christian; Köhler, Klaus (My University, 2010)
An overview of quantum cascade detector technology for the near- and mid-infrared wavelength range will be given. Thanks to photovoltaic instead of photoconductive operation, quantum cascade detectors offer great opportunities in terms of detection speed, room temperature operation, and detectivity. Besides some crucial issues dealing with fabrication and general characteristics, some possibilities for performance improvement will also be briefly presented. In a theory section, some basic considerations adopted from photoconductive detectors confirm the necessity of various trade-offs for the optimization of such devices. Nevertheless, we will show several possible measures to push the key performance figures of these detectors closer to their physical and technological limits.
Keywords: Intersubband photodetectors; quantum cascade detector; high-speed semiconductor photodetectors